Book Review: Espaço e economia. Geografia econômica e a economia política [Space and economy. Economic geography and political economy], by Floriano Godinho de Oliveira, Leandro Dias Oliveira, Regina Helena Tunes e Roberto Moraes (Org.) - Zanotelli, Claudio (Geografares, 2019)
Book Review: Espaço e economia. Geografia econômica e a economia política [Space and economy. Economic geography and political economy], by Floriano Godinho de Oliveira, Leandro Dias Oliveira, Regina Helena Tunes e Roberto Moraes (Org.) The book publishes texts presented at the III Colóquio Espaço-Economia: "Transformações no capitalismo mundial e a produção social do espaço: novos arranjos territoriais e a economia política do desenvolvimento" [Space-Economy Colloquium: "Transformations in world capitalism and the social production of space: new territorial arrangements and the political economy of development"], held at UERJ, in Rio de Janeiro, between the June 10th and 12th, 2019. The book has 19 chapters grouped into four parts that deal respectively with: New paths of scientific, technological and industrial development; Spatial restructuring, metropolization, innovation and economic-regional development; Policy, social organization of the territory and technical networks and Processes of financialization and dispossession of the territory.